1950
DOI: 10.1063/1.1747905
|View full text |Cite
|
Sign up to set email alerts
|

X-Ray Dose Determinations with Chloral Hydrate

Abstract: The chemical effects of x-rays on aqueous solutions of chloral hydrate (CCl3CH(OH)2) have been studied. The primary reaction is the conversion of the organic halogen to HCl and the resulting changes in electrical conductance have been used for the determination of x-ray dosage. The change in conductance is linear with x-ray dose and independent of dose-rate over a wide range. This compound has been used to determine the total output and depth-dose curves from a high intensity beryllium window x-ray tube.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
0

Year Published

1951
1951
1970
1970

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(6 citation statements)
references
References 2 publications
0
6
0
Order By: Relevance
“…I:rom the FIG. 1. Relation between specific co~lductance and acid concentration: 0 hydrochloric acid solutions;…”
Section: Resultsmentioning
confidence: 99%
“…I:rom the FIG. 1. Relation between specific co~lductance and acid concentration: 0 hydrochloric acid solutions;…”
Section: Resultsmentioning
confidence: 99%
“…11) and tribromoethar~ol and by about for solutions of clibromoacetaldehyde, showing that besides hydrobromic acid appreciable quantities of other strongly acid products are formed from these compounds; these products are probably bromine-substituted acetic acids. I t has been reported that the yield of acid from aqueous solutions of chloral hydrate is about : 3OyO greater than the yield of chloride when they are irradiated with either Coca gamma rays (12,13) or SrgO beta rays (13). No systematic attempt has been made to determine niealtly acicl products from our irradiations; a single determination of the acid formed from a solution of bromal hydrate (1020 rads/min) using both bromophenol blue ancl bromocresol purple as indicators gave a 1'7y0 greater yield with the latter inclicator; carbon dioxide was removed from the solution before titrating.…”
Section: Ilcid Yield F R O M Air-saturated Solz~tionsmentioning
confidence: 99%
“…This Inay be largely overcome by using dilute aqueous solutions of organic halogen co~npounds, for example, chloral hydrate (12). T h e Can.…”
Section: Orgaizic Iialogen Compoz~nds I N Dosimetrymentioning
confidence: 99%
See 1 more Smart Citation
“…I n 1950 Andrews and Shore (1) reported that aqueous chloral hydrate \vas decomposecl by X rays to yield I-ICI and other products. The acid yield, measured conducto~netrically, \vas found to be linear with radiation dose, and to increase with increasing te~nperature ancl initial chloral hyclrate concentration, but was reported to be independent of dose rate.…”
mentioning
confidence: 99%